Rancang Bangun Robot Berkaki Enam Berbasis Mikrokontroler - Mahendrayuda, I Gusti Ngurah Agung; Resmana, Susianto Tri; Martadinata, Yuwono (Jurnal GEMATIKA, 2009)
Mechatronics appearance with presentation of robot as a form of its implementation making development of robotics world increasingly extends. To keep abreast with the robot development that is really fast in the world then The Hexapod Robot Base On Microcontroller is made. Differs from robot using wheel in general, robot using six-legs requires more complex calculation to do movement. Microcontroller is a complete system microprocessor in a single chip. The Hexapod Robot Base On Microcontroller is made with two servos and censor to detect barrier. But there is some problem that make the robot don.t run as desired.